Indonesia’s Capital Expenditure and Economic Growth 1990-2020: Role of Accountability - Setiyanto, Aris (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2021)
This study examines the empirical relationship between capital expenditures and economic growth. It examines whether capital expenditures and accountability complement each other to encourage Indonesia's economic growth throughout 1990-2020. Using the autoregressive distributed lag (ARDL) bounds test, this study finds a cointegrated relationship between capital expenditure and economic growth in Indonesia during this period. In particular, capital expenditures have a negative impact on long-term growth. However, it is interesting that government capital expenditure with accountability shows a positive and significant effect on long-term growth. This demonstrates the importance of government accountability in managing government capital expenditures. This study implies that the government needs to increase accountability for the capital expenditures that have been realized to provide optimal benefits for Indonesia's economy in the long term.